Pengaruh Tingkat Pengetahuan Pasien Pra Operasi SC Sebelum dan Sesudah diberikan Pendidikan Kesehatan Tentang Mobilisasi Dini di Rumah Sakit Mitra Husada Tangerang Tahun 2022 - Haq, Yogie Erlangga; Lestari , Puji; Nurul Falah, Eva Siti (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
ABSTRACT Knowledge and understanding of the importance of early mobilization is necessary for postoperative patients. One's knowledge also affects the behavior of early mobilization in postoperative patients. Several factors influence the patient's understanding of the importance of early postoperative mobilization activities including age, education, and occupation. Research Objectives: To determine differences in the level of knowledge of preoperative sectio caesaria patients about early mobilization before and after being given health education at Mitra Husada Hospital Tangerang in 2022. The design of this study uses a Quasy Experimental Design research design with the aim of knowing an effect that arises, as a result of certain treatments. The design used is One Group Pretest Posttest Design. Sampling in this study using a non-probability sampling technique with a purposive sampling approach with a total sample of 58 samples. The instrument used is a questionnaire and statistical tests using the T-test with normal distributed data. The results of the study: showed that there was an influence on the level of knowledge of preoperative sectio caesarea patients before and after being given health education about early mobilization at Mitra Husada Hospital Tangerang in 2022, with a value of Sig. (2-tailed) which is 0.001 so the P Value is smaller than (0.05). Suggestion: it is hoped that it can be experience, can be useful knowledge for respondents, especially in terms of doing early postoperative mobilization.